Marine and Fisheries Development Policy After the Enactment of the Job Creation Act - Anshari, Firman Akbar; Afriansyah, Arie (SASI, 2022)
Introduction: In 2020, the Government of Indonesia enacted the Job Creation Law (UU Cipta Kerja). The government drafted the law to assist Indonesia’s economic development to attract investors to invest in Indonesia. When the omnibus law was rolled out for several laws into one, the marine and fisheries industry sector showed signs of decline in terms of utilization, which will have a negative impact on the sector.Purposes of the Research:  The article observes the Marine and Fisheries sector issues after enacting the Job Creation Law. This law dramatically impacts the fishers’ communities living in coastal areas and the marine environment. After that, questions will arise regarding the fate of fishers, coastal areas, and the marine environment after enacting this Job Creation Law.Methods of the Research: This writing was written using normative data collection methods such as books, journals, laws and regulations, and other sources that helped the author in completing this article.Results / Findings / Novelty of the Research: The results showed that, in the lives of coastal communities, especially small-scale fishers; coastal areas affected by regulatory changes; and the abolition of the Komnaskajiskan, which is needed for optimizing the assessment of fish resources in the context of determining the potential and number of allowable catches, lastly related to the marine environment which is also affected by the simplification of regulations that became the Job Creation Law.